Hepatic stellate cells increase the immunosuppressive function of natural Foxp3+ regulatory T cells via IDO-induced AhR activation. Issue 2 (31st August 2016) - Kumar, Sudhir; Wang, Jiang; Thomson, Angus W; Gandhi, Chandrashekhar R
Abstract: Immunosuppressive, naturally occurring CD4 + CD25 + forkhead box p3 + (Foxp3 + ) regulatory T cells (nTregs ) offer potential for the treatment of immune-mediated inflammatory disorders. However, potential instability of ex vivo-expanded nTregs following their adoptive transfer may be a significant limitation. LPS-stimulated hepatic stellate cells (HSCs) induce expansion and enhance the suppressive function and stability of allogeneic nTregs . We aimed to delineate mechanisms underlying HSC-induced expansion and increased potency of nTregs . HSCs and nTregs were isolated from mouse livers and spleens, respectively. Following coculture with LPS-pretreated allogeneic HSCs (LPS/HSCs), proliferation of nTregs was measured by CFSE dilution, and Foxp3 expression and acetylation were determined by immunoprecipitation (IP) and Western blotting analysis. Expression of various genes associated with immunologic tolerance was determined by quantitative RT-PCR (qRT-PCR). LPS stimulation increased the expression and activity of the immunoregulatory enzyme IDO1 in HSCs, and LPS/HSCs stimulated aryl hydrocarbon receptor (AhR) signaling in cocultured nTregs . Reciprocally, Tregs increased IDO1 expression in HSCs. IDO1 −/− LPS/HSCs were inferior to WT LPS/HSCs in stimulating nTreg expansion. Pharmacologic inhibition of IDO1 in HSCs by 1-methyltryptophan (1MT) inhibited LPS/HSC-induced AhR signaling in nTregs, which was responsible for their expansion, Foxp3 expression, and stabilization of Foxp3 by increasing acetylation of lysine residues. Finally, HSCs cryopreserved, following 2–3 passages, were as potent as primary-cultured HSCs in expanding nTregs . In conclusion, LPS/HSCs expand allogeneic nTregs through an IDO-dependent, AhR-mediated mechanism and increase their stability through lysine-acetylation of Foxp3. nTregs expanded by cryopreserved HSCs may have potential for clinical use.